EVALUATION OF THE PROTECTIVE EFFECT OF NIGELLA SATIVA (BLACK CUMIN) OIL AGAINST VANCOMYCIN-INDUCED NEPHROTOXICITY IN RATS - OMRAN, SARAH T; H AHMED, JAWAD (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The study was designed to investigate a possible protective effect of Nigella sativa (NS) against vancomycin (VAN)-induced nephrotoxicity in rats. Methods: Twenty-eight adult male Albino rats were randomly divided into four groups; seven rats in each. Group I (control): The animals were treated with normal saline (2 ml/kg/day) given orally and intraperitoneally (IP); Group II: VAN was given at a dose of 400 mg/kg/day for 7 days IP and normal saline orally; Group III: NS oil was given at a dose of 2 ml/kg/day for seven days orally and normal saline IP; and Group IV: VAN 400 mg/kg/day IP in combination with NS oil 2 ml/kg/day orally for 7 days. Twenty-four hours after the last dose, the animals were sacrificed, and serum was collected to estimate urea and creatinine. Then, both kidneys were excised, one for homogenate preparation to estimate renal tissue malondialdehyde (MDA), glutathione (GSH) and neutrophil gelatinase-associated lipocalin (NGAL) and the other for histopathological examination. Results: NS significantly decreased serum urea and creatinine compared to VAN treated group, p<0.001. NS significantly increased renal tissue GSH compared to VAN treated group p<0.001. NS lowered MDA and NGAL levels in the homogenate of renal tissues compared to their elevated levels in rats treated with VAN, but this did not achieve statistical significance. NS also ameliorated renal histopathological changes induced by VAN. Conclusion: NS has a protective effect against VAN-induced nephrotoxicity.